The impact of sports mega-events on health and environmental rights in the city of Rio de Janeiro, Brazil - Rodrigo Machado Vilani; Carlos José Saldanha Machado (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract The aim of this study is to discuss the contradictions of the Olympic Games legacy for health and environment in the city of Rio de Janeiro, Brazil. Public policies for sports mega-events have been criticized for contributing to and deepening the city's historical socio-spatial inequalities. Based on document research and data analysis, the article focused on establishing a proposal for a sustainable city, as provided in Law 10,257/2001, the so-called City's Statute. The article concludes with remarks on Olympic urban planning, its market orientation, and failures to overcome public health and environmental sanitation problems that will persist as a legacy after 2016.